Faktor yang Berpengaruh Pada Auditor Switching (Studi Pada BUMN Yang Listing di BEI 2018-2020) - Zety Ma'summah (JFAS : Journal of Finance and Accounting Studies, 2022)
This study aims to examine the effect of financial distress, management turnover, KAP size, partial audit opinion on auditor switching. The sample technique used in this study uses purposive sampling and obtained a sample of 48 BUMN companies listed on the IDX in 2018-2020.  Data analysis used logistic regression method.  The test results show that the audit opinion has no effect on auditor switching due to the significance level of 0.466, greater than 5%.  KAP size has no effect on auditor switching because the significance level value is 0.763, which is greater than 5%.  Management changes have no effect on auditor switching due to value.  The significance obtained is 0.941, greater than 5%. Financial distress has no effect on auditor switching because the significance value is 0.243, which is greater than 5%.  Key words: Auditor Switching; Audit Opinion; KAP Size; Management Change;Financial Distress.